H/D exchange in N-heterocycles catalysed by an NHC-supported ruthenium complex. Issue 13 (13th June 2019) - Mai, V. Hung; Gadzhiev, Oleg B.; Ignatov, Stanislav K.; Nikonov, Georgii I.
Abstract : NHC-supported trihydrides Cp(NHC)RuH3 show excellent catalytic activity in the H/D exchange of pyridine and some other N-heterocycles under mild conditions and low catalyst loading. Abstract : NHC-supported trihydrides Cp(NHC)RuH3 show excellent catalytic activity in the H/D exchange of pyridine and some other N-heterocycles under mild conditions and low catalyst loading. Of the catalysts screened, Cp(IMes)RuH3 showed the highest activity. H/D exchange in other aromatic systems also occurs with good to excellent conversions, whereas aliphatic, olefinic and acetylenic positions are much less active. This result is complementary to the significant aliphatic H/D exchange mediated by the related complex Cp( i Pr3 P)RuH3 (1 ). Mechanistic studies, supported by DFT calculations, suggest that the reaction proceeds via elimination of dihydrogen from Cp(NHC)RuH3 to give the monohydride Cp(NHC)RuH amenable to oxidative addition of C–H for aromatic (benzene and pyridine) and aliphatic (methane and ethane) substrates. Different reaction paths were revealed: a two-step route with an intermediate, a single step with a pre-reactive complex, and a reaction path branching with a bifurcation point. For pyridine, DFT calculations show that the catalyst off-loop state Cp(L)RuH(py) is less stable relative to Cp(L)RuH in the case of L = NHC than for L = i Pr3 P, Δr G (50 °C) = 2.6 kcal mol −1 vs. −9.41 kcal mol −1, respectively, which may account for the difference in reactivity of these two catalytic systems. The DFT results for the B3LYP, M06L, and SCAN functionals were benchmarked against each other and the DLPNO-CCSD(T) and DLPNO-MP2 data and discussed with respect to the determined catalytic activity and the catalyst inhibition.